1999
DOI: 10.1159/000018215
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic Risk of Bath PUVA in Comparison to Oral PUVA Therapy

Abstract: The potential carcinogenic risk of bath PUVA therapy was compared to that of systemic (oral) PUVA. An analysis of the epidemiological data on cancer risk following bath PUVA with trimethylpsoralen does not support the conclusion that bath PUVA per se is less carcinogenic than systemic PUVA with 8-methoxypsoralen (8-MOP). Pharmacokinetic studies indicate that both the concentration of 8-MOP in the target organ for PUVA carcinogenicity (skin) at the relevant time point (time point of UVA irradiation) and the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…PUVA‐bath with 8‐MOP has not yet been tested specifically. All forms of PUVA therapy with 8‐MOP, irrespective of the route of administration of psoralen, are expected to contribute to a small, dose‐dependent increase in nonmelanoma skin cancer 9,10 . The risk of melanoma is greater in patients exposed to high doses of PUVA 11 .…”
Section: Discussionmentioning
confidence: 99%
“…PUVA‐bath with 8‐MOP has not yet been tested specifically. All forms of PUVA therapy with 8‐MOP, irrespective of the route of administration of psoralen, are expected to contribute to a small, dose‐dependent increase in nonmelanoma skin cancer 9,10 . The risk of melanoma is greater in patients exposed to high doses of PUVA 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The excess risk of nonmelanoma skin cancer due to the treatment with PUVA has been shown to be considerably higher [33, 34]. There are no data defining the carcinogenic risk of 8-MOP bath-PUVA therapy, but it is likely similar to PUVA therapy [35]. To decrease the carcinogenic risk of phototherapy, patients with a history of exposure to therapeutic ionizing radiation or arsenic or a previous history of skin cancer should be excluded, along with careful shielding of noninvolved skin, particularly of the scrotum [36].…”
Section: Discussionmentioning
confidence: 99%
“…PUVA phototherapy carries a slightly increased risk for both nonmelanoma skin cancer and melanoma. [76][77][78] One large cohort study found that 15 years after the first treatment, there is approximately a fivefold increase in the incidence of melanoma. 79 A retrospective review reported the incidence for basal cell carcinoma of 0.69%, slightly higher than in age-and sex-matched controls.…”
Section: Safetymentioning
confidence: 99%